Design of the Business Intelligence Dashboard for Sales Decision Making - Murnawan; Samihardjo, Rosalin; Nugraha, Ucu (International Journal of Psychosocial Rehabilitation, 2020)
Business intelligence is a system that can help an executive or a decision-maker to analyze a fact that can become a value from a profit or sales from a different dimension. Business intelligence provides a data visualization, usually in the form of graphics or charts, that can help the decision-maker make a decision. It can also help to do trend analysis and help make an indicator when the business is off track. It can help the decision-making process, like item positioning and customer segmentation. The creation of a business intelligence dashboard can help PT. Inisiatif Mitra Mandiri to do the extensive analysis in order to make a decision, such as sales performance monitoring, item positioning and monitoring, and customer segmentation dashboard. Sales performance monitoring means that they can monitor the sales performance of a company, helping the executive to realize when their sales performance is off track and needs to be fixed. It gives a trend analysis about the sales and can help the executive detect the losses. While item monitoring can be used to monitor the items in each site that are in high demand and can be used to plan for placing and stocking the items on that site. For instance, executives can manage to make plans for item stocking on each site by looking to the previous years on which items are in high demand. For customer segmentation, it can be used to determine a profitable customer that needs to be retained, and it needs customer data from various dimensions that can help them to do the customer segmentation.